Daya Pembengkakan (Swelling power) Campuran Tepung Ganyong dan Tepung Terigu terhadap Tingkat Pengembangan dan Daya Terima Roti Tawar - Hayuningsih, Listiyani; , Dwi Sarbini, S.ST., M.Kes; , Rusdin Rauf, S.TP., M.P (2013)
Swelling power is the power of flour to inflate. canna has a good potential for bakery products because it has a high viscosity and gel strength. Organoleptic properties of white bread in canna flour including color, flavor, aroma and texture. The purpose of this research was to determine swelling power granules mixed canna flour and wheat flour on level of development and power accept of white bread. . Complete randomized design was used with addition of flour percentage (0%, 25%, 50%, 75%, 100%) and Swelling power respectively with five treatments and three replications analysis. Data swelling power and power accept were analyzed using one way anova followed by duncan's at a level 0,05. The result indicated that there was a significant different of white bread made from the mixture of canna flour ang wheat flour at various ratio. The higher the level of canna flour, the bigger the swelling power of pasta. There were differences of white bread development manufactured from various level of canna flour and wheat flour. The biggest of development level of white bread was displayed by canna flour : wheat flour (0: 100), followed by (50: 50), were 109,72% ang 47,61%, respectively.there was different significally white bread acceptance level, made from different ratio of canna flour and wheat flour. The ratio of (25: 75) gave the greatest of acceptance level. In white bread manufacturing suggested to substitute the canna flour as much as 25% of the wheat flour.